Negative impact of high body mass index on cetuximab-mediated cellular cytotoxicity against human colon carcinoma cells. (17th February 2021) - Campiotti, Leonardo; Gariboldi, Marzia Bruna; Mortara, Lorenzo; Noonan, Douglas McClain; Gallo, Daniela; Nigro, Olga; Monti, Elena; Piantanida, Eliana
Abstract: This study assessed the relationship between the ability of Natural Killer (NK) cells to activate antibody-dependent cellular cytotoxicity against human HT29 colorectal cancer cells exposed to cetuximab and the body mass index of the human subjects from whom the NK cells had been obtained. NK cells obtained from 73 human donors were co-incubated with HT-29 human colon cancer cells in the presence or absence of cetuximab. Antibody-dependent cellular cytotoxicity was assessed by measuring LDH release. A significant negative correlation was observed between body mass index and cetuximab-induced antibody-dependent cellular cytotoxicity. NK cells obtained from subjects who were overweight or with obesity were less efficient in killing cetuximab-treated HT29 cells than those derived from normal weight donors. Our results suggest that the success of cetuximab-containing regimens might be impaired in overweight and obese patients with colorectal cancer.